A PORTRAIT OF THE ENGLISH COURSE AT A FACULTY OF EDUCATION IN SUMATERA - Petrus, Ismail (Indonesian Journal of Applied Linguistics, 2012)
Abstract: English is one of the compulsory courses taught in tertiary education in accordance with Paragraph 2 Article 37 of the National Education Law No. 20/2003 and Paragraph 2 Article 9 of the Government Regulation No. 19/2005 on national standards of education. Some people believe that college English may not be taught as English for General Purposes, but it should be designed on the basis of needs analysis. As the students have learnt the basic knowledge and skills of English at secondary schools, college English should aim at building study skills or developing professionalism and specification of the students? choice. This paper depicts the existing conditions of the English course at the Faculty of Teacher Training and Education of a University in Sumatera. The portrait of the course was described in terms of such aspects as institutional goals, class management, instructional materials, instructors, teaching methodology, and evaluation. This paper was based on a study involving 378 second-semester students of 7 study programs, 10 instructors, 7 heads of study programs, 2 heads of departments, 2 faculty?s heads, and the head of the university?s language institute. The research data were collected through (a) a questionnaire given to the students, (b) interviews with the instructors, the heads of departments/study programs, the faculty?s heads, the language institute head, (c) observations in the classroom, and (d) a review of the documents. The methods of data analysis were both quantitative and qualitative. The quantitative method of analysis was first used for assessing the responses obtained; and secondly, the qualitative analysis provided the evaluation and interpretation of the figures and insights gained from the interviews, observations, and review of the documents. The results of the research showed that: (a) the English course at the faculty could be considered as General English, (b) there was no needs analysis conducted, (c) half of the instructors had master?s degrees in accordance with the Law No. 14/2005 on teachers and lecturers, (d) the teaching and learning activities were mostly lectures and question-answer sessions in the theatre seating arrangement, (e) there was no course evaluation, and (f) there was no collaboration among the study programs, instructors, and language institute in designing the course. The findings of this research would be useful for the coordinator of the English course to redesign the syllabus for a better instruction.   Key words: English course, needs analysis, English for Specific Purposes